Mathematics And Science In English: Teachers Experience Inside The Classroom - Ong , Saw Lan; Tan, May (Penerbit Universiti Sains Malaysia, 2008)
In 2003, the Malaysian government implemented a new policy in the national education system; English is made the language of instruction in schools for the teaching of Mathematics, Science and technology subjects. These subjects had formerly been taught in the Malay language. The purpose of teaching Science and Mathematics in English is to enable students to acquire proficiency in English while learning the content. This study aims to provide more in-depth information concerning teachers’ experiences and classroom practices in the implementation of the change in language of instruction for Mathematics and Science. To gather information on teachers’ experiences with the policy change, classroom observation and semi-structured interviews were conducted with the four Mathematics and Science teachers. While teachers interviewed are supportive of the policy, they are still struggling with the realities of implementing this policy. Three factors appear to be salient in influencing how quickly a teacher can effect the transition into teaching entirely in English. They are the prior educational background of teachers, the linguistic environment in school and the linguistic abilities of their students.